2021
DOI: 10.15421/022147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cameraria ohridella feeding on Aesculus hippocastanum photosynthesis

Abstract: The complex of invasive species of phytophagous insects that can adapt to novel living conditions is constantly increasing. The ecological effect of their vital activity in the new environment is almost impossible to predict. As a result, invasions undesirable in the economic sense are often observed. The horse -chestnut leaf miner (Cameraria ohridella Deschka & Dimič, 1986, Gracillariidae) is one of these problematic invader species in the introduced range of the horse chestnut (Aesculus hippocastanum (Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Extensive brown-yellow spots on leaves as well as rapid wilting and premature fall of leaves before the end of the growing season are the external symptoms of C. ohridella (horse-chestnut leaf miner) foraging [ 7 , 8 , 9 ]. As a result of infestation by many (5–7) generations of larvae of the pest, the tree is severely weakened, the photosynthetic efficiency declines, the intensity of flowering and the weight and size of fruit and seeds are reduced, and the size and vitality of developing seedlings decrease [ 10 , 11 , 12 ]. The anatomical and histochemical studies of chestnut leaves conducted to date have shown a complete absence of palisade parenchyma, damaged spongy parenchyma cells, and death of the epidermis on both sides of the leaf blade in the mine, i.e., the pest foraging site [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive brown-yellow spots on leaves as well as rapid wilting and premature fall of leaves before the end of the growing season are the external symptoms of C. ohridella (horse-chestnut leaf miner) foraging [ 7 , 8 , 9 ]. As a result of infestation by many (5–7) generations of larvae of the pest, the tree is severely weakened, the photosynthetic efficiency declines, the intensity of flowering and the weight and size of fruit and seeds are reduced, and the size and vitality of developing seedlings decrease [ 10 , 11 , 12 ]. The anatomical and histochemical studies of chestnut leaves conducted to date have shown a complete absence of palisade parenchyma, damaged spongy parenchyma cells, and death of the epidermis on both sides of the leaf blade in the mine, i.e., the pest foraging site [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a change in the activity of individual benzidine-peroxidase isomers contributes to maintaining the functional integrity of the photosynthetic system in chestnut leaves [52]. It is the inhibition of photosynthetic activity (decrease in the quantum efficiency of photosystem II) that provides violations of the coherence of the reactions of the Calvin cycle, which were recorded in infected leaves both on the illuminated and shaded sides of the crown of horse chestnut trees [53].…”
Section: Discussionmentioning
confidence: 99%
“…We examined water deficit and relative turgidity of leaves and fruits, and these parameters varied with altitude. Other researchers are also engaged in the study of water regime of the plants (Gritsan et al, 2019;Jagosz et al, 2019) and influence of water deficiency or pests (Holoborodko et al, 2021(Holoborodko et al, , 2022a(Holoborodko et al, , 2022bShupranova et al, 2021) on the physiological condition of the plants. The water circulation of elderberry plants principally depends on the conditions of the atmosphere (Tökei et al, 2005).…”
Section: Discussionmentioning
confidence: 99%